Two-way tuning of structural order in metallic glasses - Lou, Hongbo; Zeng, Zhidan; Zhang, Fei; Chen, Songyi; Luo, Peng; Chen, Xiehang; Ren, Yang; Prakapenka, Vitali B.; Prescher, Clemens; Zuo, Xiaobing; Li, Tao; Wen, Jianguo; et al. (Nature communications, 2020)
Metallic glasses are expected to have quite tunable structures in their configuration space, without the strict constraints of a well-defined crystalline symmetry and large energy barriers separating different states in crystals. However, effectively modulating the structure of metallic glasses is rather difficult. Here, using complementary in situ synchrotron x-ray techniques, we reveal thermal-driven structural ordering in a Ce 65 Al 10 Co 25 metallic glass, and a reverse disordering process via a pressure-induced rejuvenation between two states with distinct structural order characteristics. Studies on other metallic glass samples with different compositions also show similar phenomena. Our findings demonstrate the feasibility of two-way structural tuning states in terms of their dramatic ordering and disordering far beyond the nearest-neighbor shells with the combination of temperature and pressure, extending accessible states of metallic glasses to unexplored configuration spaces. While metallic glasses are expected to have tunable structures, these have rarely been demonstrated. Here, the authors combine temperature and pressure to show a two-way structural tuning in rare earth-based metallic glasses beyond the nearest-neighbor atomic shells.